2019
DOI: 10.1002/pssb.201800636
|View full text |Cite
|
Sign up to set email alerts
|

Temperature‐Dependent Noise and Transport in Silicon Two‐Layer Nanowire FETs

Abstract: Silicon two-layer (TL) nanowire (NW) field-effect transistors (FETs) are fabricated by applying a CMOS-compatible top-down approach to silicon on insulator (SOI) wafers with additionally epitaxially grown silicon layers. Transport and noise properties of fabricated structures with p-type conductivity are studied in a wide temperature range (100-300 K). A random telegraph signal (RTS) noise as a special case of trapping-detrapping processes is registered as a dominant noise component at room temperature. A shif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
(37 reference statements)
1
3
0
Order By: Relevance
“…Unlike in all metal/insulator/metal devices previously studied, if the bias is held constant a cyclical filament formation and disruption at random times occurs (see Figure 5b). More importantly, the mean on/off current ratio statistically observed in Figure 5b is >100, which is the highest ever reported in the literature for a random signal of telegraphic characteristics when compared not only to other reports on h‐BN [ 12,37,47,54 ] but also TMOs, [ 11,52,55,67–72 ] ultra‐scaled transistors [ 73–78 ] and nanowires [ 79–87 ] (see Figure 5c). This behavior, which remains stable over time, cannot be strictly called RTN because this term has been always employed in the literature to refer to charge trapping and de‐trapping, while here it is related to ionic movement; hence, we propose to call it random telegraph signal (RTS)‐like current.…”
Section: Resultssupporting
confidence: 50%
“…Unlike in all metal/insulator/metal devices previously studied, if the bias is held constant a cyclical filament formation and disruption at random times occurs (see Figure 5b). More importantly, the mean on/off current ratio statistically observed in Figure 5b is >100, which is the highest ever reported in the literature for a random signal of telegraphic characteristics when compared not only to other reports on h‐BN [ 12,37,47,54 ] but also TMOs, [ 11,52,55,67–72 ] ultra‐scaled transistors [ 73–78 ] and nanowires [ 79–87 ] (see Figure 5c). This behavior, which remains stable over time, cannot be strictly called RTN because this term has been always employed in the literature to refer to charge trapping and de‐trapping, while here it is related to ionic movement; hence, we propose to call it random telegraph signal (RTS)‐like current.…”
Section: Resultssupporting
confidence: 50%
“… 102 Thus, special signal processing algorithms should be often used to split noise and useful signal. 103 Antibodies are often used as bioreceptors in such nanowire-based biosensors, 104 but several enzymes were also tested. For example, GOx was immobilized on the surface of FET based on In 2 O 3 nanoribbons.…”
Section: Inorganic Nanomaterials In Enzyme-based Biosensorsmentioning
confidence: 99%
“…They might not only allow for studies and usage of new transport regimes but also a demonstration of several advantages, including a more sensitive, high-speed detection of biochemical signals [9][10][11][12][13][14] DOI: 10.1002/admt. 202301303 We have recently shown that singe-trap phenomena (STP) and noise properties of LG NW FETs might offer new time parameters [15][16][17][18][19][20][21] for biosensing applications. Using the capture time to a single trap near a semiconductor channel and the characteristic emission time enables sensitivity to be improved.…”
Section: Introductionmentioning
confidence: 99%
“…We have recently shown that singe‐trap phenomena (STP) and noise properties of LG NW FETs might offer new time parameters [ 15–21 ] for biosensing applications. Using the capture time to a single trap near a semiconductor channel and the characteristic emission time enables sensitivity to be improved.…”
Section: Introductionmentioning
confidence: 99%